Gauging the response to cardiac resynchronization therapy: The important interplay between predictor variables and definition of a favorable outcome. Issue 3 (11th January 2017) - Petrovic, Milan; Petrovic, Marija; Milasinovic, Goran; Vujisic Tesic, Bosiljka; Trifunovic, Danijela; Petrovic, Olga; Nedeljkovic, Ivana; Petrovic, Ivana; Banovic, Marko; Boricic‐Kostic, Marija; Petrovic, Jelena; Arena, Ross; et al.
Abstract : Aims: Selection of patients who are viable candidates for cardiac resynchronization therapy (CRT), prediction of the response to CRT as well as an optimal definition of a favorable response, all require further exploration. The purpose of this study was to evaluate the interplay between the prediction of the response to CRT and the definition of a favorable outcome. Methods: Seventy patients who received CRT were included. All patients met current guideline criteria for CRT. Forty‐three echocardiographic parameters were evaluated before CRT and at 1, 3, 6, and 12 months. M‐mode, 2D echocardiography, and Doppler imaging were used to quantify left ventricular (LV) systolic and diastolic function, mitral regurgitation, right ventricular systolic function, pulmonary artery pressure, and myocardial mechanical dyssynchrony. The following definitions of a favorable CRT response were used: left ventricular ejection fraction (LVEF) improvement more >5% acutely following CRT, LVEF improvement >20% at 12‐month follow‐up, and a LV end‐systolic volume (LVESV) decrease >15% at 12‐month follow‐up. Results: For the LVEF improvement >5%, the best predictor was isovolumetric relaxation time (IVRT; P =.035). For improvement of LVEF >20%, the best predictors were left ventricular stroke index (LVSI; P =.044) and left ventricular fractional shortening (LVFS; P =.031). For the drop in left ventricular systolic volume (LVESV >15%), the best predictor was septal‐to‐lateral wall delay (Δ T ) ( P =.043, RR=1.023, 95% CI for RR=1.001‐1.045). Conclusion: The definition of a favorable CRT response influenced the optimal predictor variable(s). Standardization of defining a favorable response to CRT is needed to guide clinical decision making processes.